Spatial Characteristics of Squatter Housing Areas in Jeddah City by Using GIS - Alzamil وليد; احمد هليكة; بندر; آل ملفي حسن; أبو الريش رأفت; الحربي ريان (Journal of King Abdulaziz University: Environmental Design Sciences, 2022)
Jeddah, as the gateway to the holy cities, and the Islamic port overlooking the Red Sea, has attracted many residents who have settled for decades. The emergence of squatter housing areas began with the beginning of the expansion of Jeddah. The population growth was accompanied by a lack of fulfillment of the housing need, especially with the beginnings of the economic boom and the increase in the number of immigrants, as squatter were formed and later expanded to become within the urban context of the city. This paper aims to analyze the characteristics of the spatial distribution of squatter housing areas in Jeddah using GIS. The paper concluded that squatter housing areas in Jeddah spread within four areas, which are the center of Jeddah, East Jeddah, North Jeddah, and South Jeddah. The total population of these area is 1,123,088, representing 25% of the total population of the city, and they are distributed within 63 squatter areas, occupying an area of ​​209 km2, equivalent to 25% of the total urban area of ​​the city. Finally, analyzing the spatial characteristics of squatter housing areas in Jeddah is a first step towards proposing future development strategies within the framework of the Kingdom’s 2030 vision in seeking to improve the standard of living, quality of life.